Debate on Categories of Da'wah Verses Qs. Ali Imran Verse 64 Between Buya Hamka and Mufassir Nusantara - Usamah Abdurrahman; Andri Nirwana AN; Ainur Rhain; Alfiyatul Azizah; Yeti Dahliana; Ahmad Nurrohim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article discusses the debate of ulama' Nusantara in determining the content in Qs. Ali Imran verse 64 which is categorized as mubahalah verse or da'wah verse. This difference in opinion of the 'Nusantara ulama' can cause controversy among the public, so there is a need for definite clarity in determining the content of the verse, whether it is classified as a mubahalah verse or classified as a da'wah verse? Thus, the purpose of this article is to clarify the content of Qs. Ali Imran verse 64, by comparing the opinions of the four Mufassir Nusantara through the literature study method by collecting data on the opinions of the four scholars' from various sources such as books, journals, and existing researches, as well as collecting and describing in detail verses that can be identified into the category of da'wah verses. This research resulted that Qs. Ali Imran verse 64 can be categorized as a mubahalah verse when viewed from the historical side of the descent of the verse, but this verse can also be used as a benchmark for da'wah verses because it contains elements of da'wah, including such as exclamations, in line with the purpose of da'wah, etc.